Using fuzzy expert systems for decision support in the process of post-consumer wood sorting - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2017)
It is substantiated that the most realistic and possibly the only practical approach to solving the sorting problem is the description (accumulation volumes of PCW for material or energy use, volumes by size of pollution (sorting by categories), volumes by dimensional suitability (for obtaining specification blanks) and the very procedure for making current decisions about sufficient PCW that will provide the required quantity of quality blanks, methods of the theory of fuzzy sets. Fuzzy expert is developed. Well, the decision support system for choosing a rational PCW sorting option has developed a block diagram of a logical algorithm (simulation algorithm) to determine the priority PCW sorting option. It has been established that 83% of the 92% of the material eligible for sorting by categories remains Includes the first three categories. For each category we have our own percentages of the size-suitable PCW: PCW-I is 69%, PCW-II - 66%, and PCW-III - 50%. As a result, the percentage of size-suitable PCW is 60% of 83% for material use, or 50% of all PCW, which was intended for sorting.